EDUCATORS’ PERCEPTION OF BLENDED LEARNING MODELS ON MATHEMATICS LEARNING - Ayu Faradillah; Windia Hadi (KALAMATIKA Jurnal Pendidikan Matematika, 2020)
The main objective of this research is to analyze and compare educators' perceptions of the application of the BL model in mathematics learning. The stages of research carried out in this study began with the manufacture of questionnaires both for educators and students. Next the researchers asked one of the lecturers and mathematics teachers to validate it. Based on the results of the validation conducted, the questionnaire was declared to be appropriate to be used by correcting a selection of words so it would not have a double meaning. In the next stage, researchers distributed the questionnaire to educators in schools and universities in several provincies in Indonesia After obtaining the data, researchers analyzed the data using WinStep. The results of the questionnaire showed that there was one question on the questionnaire that was difficult to be agreed upon by lecturers and teachers, namely the 16th statement that revealed students felt they needed more time to complete online assignments when dealing with graphics / diagrams / tables / other on mathematical material